Maximising the Potential of Reactive Carbon Support with Cobalt Active Phase for the Oxygen Evolution Reaction - Termeh Darvishzad; Paweł Stelmachowski (Molecules)
A growing interest in novel noble metal-free electrocatalysts is fuelled by the pressing need to overcome the drastic demand for sustainable energy sources. To this end, the oxygen evolution reaction (OER) utilising transition metal oxide–carbon composites in alkaline media is considered a robust technology. In many such systems, carbon is used as a conductive additive or support, and the interactions between carbon support materials and the active phase affect the efficiency of the electrocatalyst. Cobalt forms some of the most active and stable electrocatalysts for OER. In carbon-supported systems, the dispersion of the cobalt phase on the carbon surface is a key factor in influencing the catalyst activity in water-splitting reactions. In this study, a low-temperature plasma treatment is used to boost the efficiency of the cobalt active phase by functionalising the carbon support with various oxygen groups. We used a simple deposition–precipitation method to obtain cobalt hydroxide active phase over graphene nanoparticles. The activation of graphene nanoparticles with oxygen plasma allowed us to obtain a catalyst that showed only 317 mV@10 mA·cm−2. More importantly, in the series of plasma-activated samples, the OER activity was very high in a range of cobalt phase loadings, yielding a material with 2.4 wt.% of cobalt and an overpotential of only 327 mV@10 mA·cm−2. The results indicate that plasma activation of GNP support maximises the usage of the transition metal active phase, which allows for an improvement in area-normalised and a dramatic improvement in the mass-normalised OER electrocatalytic activity.